Criminal law protection of the right to life that is 'not worth living' - Drakić Dragiša (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2013)
In this paper the author deals with an issue of the criminal law protection of the right to life of two categories of persons whose life, in the opinion of some scholars, is not worth living. A common feature to all such persons is that they are not 'dying' patients; however their prospects of living are very poor while the quality of their lives is very low. The author points out that a question, whether a certain act that caused a person's death, is the act of a murder, depends on whether such person - an object of criminal act had the right to life at the moment such act was undertaken. That person possessed such right [to life], provided that the form of his life was valued as a life at that moment. The principle task that the author put before himself is to answer a question whether different forms of life described in this paper possessed the value of the life, and depending on the answer, whether such forms of life enjoy the criminal law protection. Almost the entire paper is dedicated to the critique of authors whose intention is to emerge with a unifying criteria regarding which life is 'worth' living and which is 'not worth' living. The author's position is that such criteria are not suitable when it comes to the criminal law protection of life. It is the conclusion of the author that criminal law should offer equal protection to each human life, regardless of its quality and despite of its ability to exist independently and the prognosis of survival in the future. Therefore, there is no life that, in general, would be excluded from the protection offered by the criminal law. This does not mean that in certain cases some actions that have resulted in a death of a gravely indisposed person may be excluded from the scope of the criminal law sanction. However, we may not embrace general criteria on which kind of human life is 'worth' living and which is 'not worth living' but rather each case must be examined independently by applying the above stated principle supported by the author in this paper.